Investigating basic channel routing matrix using reaper: designing a surround sound 5.1 instruction model for learning - Ardy Aprilian Anwar; Riky Taufik Afif; Md Nagib Bin Padil (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
The production and processing of surround sound are only done in the post-production department for movie and home theaters. In our country, there has been no specific teaching on surround sound systems, especially in channeling. We use matrix routing to define the DAW's channel flow arrangement on the soundtrack. Surround Sound spatial sound processing is indispensable for improving film production in Indonesia. Inspired by Dolby Surround, we independently investigated the matrix channeling on the Reaper DAW to identify the specific settings for getting ready audio mixing conditions with a 5.1 surround system. Specific tools are needed to understand large and complex data sets to understand processes. We went through several experiments and time to understand this, collecting observational data through recording and thinking hard until finally, we poured the process into a model of teaching materials. We offer channel patching on some audio interfaces. The design of teaching materials implemented the findings of this study. Furthermore, the teaching material model can be equipped, used, and adjusted to the conditions of the place of study.